Fault Diagnosis Expert System for Critical Systems and Components of “Shenhua” Electric Locomotive - GAO Yongqiang (Kongzhi Yu Xinxi Jishu)
In view of the difficulties and poor efficiency of manual troubleshooting of locomotive faults, this paper proposed a method for correlative analyses of traction converter faults and train level faults. The method is based on a fault diagnosis model that utilizes the expert knowledge of locomotive fault diagnosis and can realize intelligent diagnosis of locomotive faults. The fault diagnosis expert system of Shenhua electric locomotive traction converter and other subsystems is implemented. Experimental results show that the accuracy of fault diagnosis for the key systems and components of Shenhua electric locomotive can reach 90%, which meets the requirements of intelligent operation and maintenance of railway.